Why We Should Avoid Artists Who Cause Harm: Support as Enabling Harm - Elicker, Bradley (Journal of Applied Philosophy, 2021)
This article examines our ethical responsibility toward artists engaged in harmful behaviors. Specifically, I demonstrate when and why we are morally obligated to withdraw our public and financial support from Artists Who Cause Harm such as Louis C.K., Terry Richardson, and Ryan Adams. Using a moral distinction presented by Philippa Foot and others, I identify this support as enabling harm when the wealth and influence that we support removes typical barriers that protect victims from harm and interposes barriers that prevent victims from avoiding harm. I proceed to demonstrate that our personal support is morally significant, and we have a moral responsibility to make contributions to collective action when the cost is low or the degree of belief that others will contribute is high. Here we have both a strong belief that others will withdraw support and a relatively low cost to ourselves to do so. I acknowledge that enabling current harms is only a sufficient condition to withdrawing support from an artist and should not minimize other reasons for avoiding certain artists and their works. However, when we do believe that our support enables an artist engaged in harmful behaviors, we have an obligation to withdraw that support.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/japp.12467
Keywords: Bibliographie

Accounting For the Limited Success of #MeToo in the Popular Music and Stand-Up Comedy Industries - Worden, Chris; Gjika, Anna (Cultural Sociology, 2023)
Despite several high-profile cases and years of #MeToo activism, a lack of systemic change and consistent consequences for many alleged offenders has led journalists and fans to wonder when the popular music and stand-up comedy industries will truly have their ‘MeToo moment.’ In this article, we explain that this moment has already arrived, but has produced inconsistent results in these industries due to the unique cultural and structural obstacles they share, and which frustrate civil sphere actors’ attempts at civil repair. Our analysis draws on Jeffrey C. Alexander’s (2018, 2019) theory of societalization – the process by which institutional crises come to be seen as social problems that demand the intervention of civil sphere actors. We argue that where #MeToo and the popular music and stand-up comedy industries are concerned, the process of societalization has been (and will likely continue to be) ‘blocked’ or ‘stalled’ (Alexander, 2018, 2019). We suggest that the potential for societalization is reduced due to a combination of the arts sphere’s anti-civil values and weak institutionalization in the popular music and stand-up comedy industries.
Publisher: SAGE Publications
Keywords: Bibliographie

Working girl: on selling art and selling sex - Giovannitti, Sophia (Verso, 2023)
"Giovannitti argues that if we delve into our anxieties around art and sex, we can find new ways to live and spaces of freedom"–
Keywords: Bibliographie; Nettoyer

Sans consentement : trente scandales sexuels qui ont changé le Québec - Morin, Michel (2024)
Depuis l'arrivée de #MoiAussi et des autres mouvements de libération de la parole, on a assisté au Québec à une succession de scandales sexuels impliquant des personnalités publiques, figures respectées et influentes qui avaient abusé de leur pouvoir, parfois des décennies durant. Michel Morin fait un pas de côté pour revisiter ces histoires encore sensibles, en portant une attention particulière à leur traitement médiatique. Avocat de formation, il se penche aussi sur le fonctionnement du système judiciaire et son impact sur le processus de dénonciation. Sans s'ériger en juge, l'auteur laisse parler les faits, bien souvent accablants, dans un essai qui permet de prendre la mesure de ce qui a été trop longtemps ignoré, voire toléré, et du chemin qui reste à parcourir.
Keywords: Bibliographie; Nettoyer

Simple Plan renvoie son bassiste de tournée suite à des allégations d’inconduites sexuelles contre lui - Bibeault, Matt (99scenes, 2020)
C’est la firme de management de Simple Plan, Coalition Music, qui a confirmé la nouvelle. Chady Awad avait justement remplacé David Desrosiers lorsque ce dernier avait pris une pause de SP pour traiter sa dépression de 2017 à 2019. Awad était également photographe et vidéaste pour Simple Plan. Simple Plan a mis fin à sa... View Article
Keywords: Bibliographie; Nettoyer

Masculinity, Intersectionality and Identity: Why Boys (Don’t) Dance - Risner, Doug; Watson, Beccy (Springer International Publishing, 2022)
Keywords: Bibliographie; Nettoyer

Super Fluid/Super Black: Translations and Teachings in Transembodied Metaphysics - Whitson, Ni’Ja (Critical Black Futures: Speculative Theories and Explorations, 2021)
Ni’Ja Whitson turns a piece that was originally commissioned as a keynote lecture for the 2020 Collegium for the African Diaspora Dance (CADD) conference, Fluid Black: Dance Back. This chapter is a hybrid text that centralizes Black Transgender and Nonbinary experiences in a conversation of futurity in African Diasporic spirituality, dance traditions, and performativities. Furthermore, Super Fluid/Super Black interrogates beingness through an exploration of astrophysics and global attempts at Black erasure to uncover new strategies of collectivizing under physical, metaphysical, and cosmic bodies that dismantle cisheteronormativity at their core.

How is the Ballet World Including Non-Binary Dancers? - Lund, Rebekah (Dance Major Journal, 2022)
A few pioneers have shown the way, but who will follow?
Keywords: Bibliographie; Nettoyer

Unsettling homocolonial frames of remembrance: Two-Spirit and Indigiqueer interventions at the museum - Failler, Angela (Memory Studies, 2023)
This article considers a Two-Spirit and Indigiqueer protest at the Canadian Museum for Human Rights as a flashpoint that exposes problems with how memory-making institutions are incorporating lesbian, gay, bisexual, trans and queer issues into their programming and/or collections. The protest brings into relief the museum’s investment in a homocolonial framing of remembrance for the way in which the telling of lesbian, gay, bisexual, trans and queer ‘progress’ is entangled with a settler colonial political economy wherein the tokenistic inclusion of some queers into the sexual citizenry happens alongside the dispossession, devaluing and criminalizing of others. I then undertake some preliminary ‘curatorial dreaming’ upon two other interventions–commentaries uploaded to a digital story bank by a Two-Spirit and an Indigenous queer museumgoer, and the short film Woman Dress by Plains Cree artist TJ Cuthand. Along with the protest, the commentaries and the film unsettle homocolonial frames of remembrance and provide critical openings towards decolonial queer memory work at the museum.
Keywords: Bibliographie; Nettoyer

Dancing Boys and Men: Negotiating Masculinity and Sexuality - Christofidou, Andria (Masculinity, Intersectionality and Identity: Why Boys (Don’t) Dance, 2022)
Theatrical dance remains widely perceived as an unconventional activity for boys and young men in many Western contexts. This chapter focuses on professional male dancers’ pathways into recreational, pre-professional dance and assesses the various obstacles encountered and the sources of encouragement available to continue dancing and to pursue a dance career. Data analysis challenges the assumption that homophobia and hierarchies among boys, men, and masculinities have been erased. The chapter argues that wider systems of inequality, oppression, and power persist. These continue to affect boys and young men, influencing their choices and the possibilities to transgress gender norms.

Hypermasculinity Makes the Queer Boy Faint - Alterio, Anthony M. (Masculinity, Intersectionality and Identity: Why Boys (Don’t) Dance, 2022)
Through the lens of personal experience, this chapter provides an exploration of the oft-concealed practices and hypermasculine ideals in dance education. Commercial, concert, and academic dance pedagogy continues to create and perpetuate homophobia that restricts the definition of “boy dancer” to the point of creating a false scarcity and competition to be the most cis-heteronormative male possible. Alterio argues this environment contributes to the perpetuation of discrimination against LGBTQIA+ dancers, the exclusion of non-cis boys, and lack of innovation in the field. Recommendations are offered to those interested in pushing the boundaries of performance and gender identity and a call for institutions to support this work.
Keywords: Bibliographie; Nettoyer

High time to enhance dancer welfare: a call to action to improve safeguarding and abuse prevention in dance - Cumming, Jennifer; Nordin-Bates, Sanna M.; Johnson, Carrie; Sanchez, Erin N.; Karageanes, Steven J. (BMJ Open Sport & Exercise Medicine, 2024)
While there is a lack of research into abuse in elite dance, numerous allegations of emotional, sexual and physical abuse of dancers can be found anecdotally in the media, legal convictions and personal accounts. As more dancers speak out, the scale of the problem within preprofessional schools and professional companies is becoming apparent. Accordingly, effective safeguarding mechanisms for preventing, identifying and reporting abuse are urgently needed. This viewpoint is intended to raise health professionals’ awareness of factors contributing to abusive practices found in dance environments and the potential clinical implications of abuse to dancers’ health and well-being. We also call for research and policy engagement on safeguarding and abuse prevention designed and implemented in partnership with stakeholders, aiming to promote safe and positive dance environments for all.
Publisher: BMJ Specialist Journals Section: Viewpoint

Personal Safety for Dance (2022)
Personal Safety for Dance exists to develop a dance environment that is free from abuse, open, and supportive for all in dance.
Keywords: Bibliographie; Nettoyer

Je n'en ai jamais parlé à personne - Delvaux, Martine (Éditions Heliotrope, 2020)
«En octobre 2017, devant la vague de témoignages suscitée par le mouvement #moiaussi, j’ai senti une urgence : une fois sorties du silence, nous ne devions pas y retourner. C’est la raison pour laquelle j’ai lancé un appel. Ce livre est une chambre d’échos. Un chœur. Sans déesse ni héroïne en tête, des voix avancent. Nous faisons front commun.» Martine Delvaux «Je n'en ai jamais parlé à personne» : paroles recueillies et agencées par Martine Delvaux
Keywords: Bibliographie; Nettoyer

Diversity, Equity, Inclusion & Belonging Committee (ACTRA National, 2023)
ACTRA National’s Diversity, Equity, Inclusion & Belonging Committee promotes the principles concerning the casting of People of Colour, Indigenous Peoples and people with disabilities. The best initiatives are driven by members. We can better shape initiatives to support you by getting to know our membership and understanding your experiences. We welcome your input and your […]
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Women's Committee (ACTRA National, 2023)
The best initiatives are driven by members. By getting to know the membership and listening to your experiences, we can better shape initiatives that support you. Does your ACTRA Branch have a Women’s Committee? Find out by contacting your Branch office or contact the National Women’s Committee if you would like to get one started. […]
Keywords: Bibliographie; Dans le rapport

Progress Pride Committee (ACTRA National, 2023)
ACTRA National is proud to be launching the ACTRA National Progress Pride Committee. The inaugural Committee meeting took place on Friday, May 26th, 2023. Mandate The mandate of the committee is to address issues that impact the Queer ACTRA membership across the country, and to build a National community through the sharing of relevant information […]
Keywords: Bibliographie; Dans le rapport

Believability: sexual violence, media, and the politics of doubt - Banet-Weiser, Sarah; Higgins, Kathryn Claire (Polity Press, 2023)

Unsafe words: queering consent in the #MeToo era - Buggs, Shantel Gabrieal; Hoppe, Trevor (Rutgers University Press, 2023)
"What can the #MeToo moment teach queers about consent? And what can queers teach the rest of the world about ethical sex? This radical book brings together academics, activists, artists, and sex workers to tackle dangerous questions about sex, power, consent, and harm.While the authors in this volume are committed to promoting consensual, pleasurable sex, we reject heteronormative, one-size-fits-all models of consent and sexual ethics.#MeToo ushered in an era of reckoning and accountability for one powerful man after another. But too often it has defined sex and harm in starkly heterosexual-and often white and wealthy-terms."Unsafe Words" tells a queerer side of the #MeToo story. Not all of us seek safety in sex. Nor do we all believe "enthusiastic" models of consent are practical or appropriate for some queer communities. We look instead to the tools queer communities have developed themselves to practice ethical sex-from the sex worker negotiating with her client to the gay man having anonymous sex in the backroom. We also consider how queers can better respond to sexual violence. How can our communities do better at responding to and preventing sexual violence?This challenge is especially daunting in a world where the only recourse made available is typically law enforcement, a pillar of American racism, transmisogyny, and homophobia.How can our communities imagine different responses to sexual violence that do not depend on the law to serve justice?The "unsafe words" in this volume challenge dogmatic assumptions about sex and consent while exploring tools and language to promote better, more ethical, and more pleasurable sex for everyone"– Provided by publisher

Sex, consent and justice: a new feminist framework - Sikka, Tina (Edinburgh University Press, 2022)

Cultural sexism: the politics of feminist rage in the #metoo era - Savigny, Heather (Bristol University Press, 2020)

#MeToo and beyond: perspectives on a global movement - Alcalde, M. Cristina; Villa, Paula-Irene (University Press of Kentucky, 2022)

Commande un Angelot (2021)
« Le protocole d’accréditation Commande un Angelot a été conçu afin de s’attaquer aux violences à caractère sexuel dans les bars et les événements festifs ou sociaux. Celui-ci vise à prévenir ces situations et à venir en aide aux personnes en difficulté. Le Collectif social, un organisme sans but lucratif qui souhaite déployer et soutenir la réalisation d’initiatives de nature communautaire ou sociale qui répondent aux besoins des communautés étudiantes des établissements d’enseignement supérieur, est derrière ce projet. »
https://www.commandeunangelot.com
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Répertoire des formations de groupe - Groupe de recherche et d’intervention psychosociale (2023)
«Les formations qu’on offre s’adressent principalement aux professionnel.le.s des milieux scolaires, secondaires et postsecondaires et aux professionnel.le.s de milieux variés où l’information sur les drogues est pertinente (milieux festifs, milieux d’intervention, etc.). Elles peuvent également être offertes directement à la population étudiante des milieux d’éducations postsecondaires (Formation générale aux adultes, formation professionnelle, collégiale ou universitaire). L’approche employée dans la création et l’offre de formation est toujours celle de réduction des méfaits. Nos formations abordent des thèmes tels que les violences à caractère sexuel, le consentement, les effets des substances, la prévention et la réduction des méfaits, les bandelettes de détection de Fentanyl et Naloxone, l’intervention en milieu festif, les drogues et la performance académique, ainsi que de nombreux autres sujets pertinents. »

Dénoncez un incident sur le plateau (ACTRA Montreal, 2024)
Grâce aux rapports anonymes, nous sommes informés des problèmes au fur et à mesure qu’ils surviennent. Il est possible de rester anonyme, mais il est préférable de laisser vos coordonnées pour que nous puissions vous contacter. Nous ne donnerons jamais suite à une réclamation sans votre consentement!
Keywords: Bibliographie; Nettoyer

Coordonnateur·rice·s de l'intimité - ACTRA Montréal (ACTRA Montreal, 2024)
Les coordonnateurs d'intimité sont des spécialistes de la production qui planifient, supervisent et coordonnent les scènes intimes filmées.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Against Sexual Violence in the Museum: Art, Curating, and Activism - Perry, Lara; Krasny, Elke (Journal of Cultural Analysis and Social Change, 2022)
Depictions of sexual violence are frequently found in the collections and displays of art museums, and material that represents and affirms violence against women often is displayed unchallenged. This article poses questions about how the presence of this material has been addressed in the relations between feminist activism against sexual violence, art made by artists responding to and participating in feminist activism, and the curatorial activities that have arisen to address the challenges that these activities present to art museums. The chapter investigates the 2021 exhibition Titian: Women, Myth and Power at the Isabella Stewart Gardner Museum and its handling of themes of rape in the central exhibit, Titian’s Rape of Europa; the history of themes of rape in feminist art since the 1970s and in exhibitions of this art that have taken place in museums in the last two decades; and curatorial engagements with sexual violence and rape in recent art exhibitions in the US and in the UK. The article argues that new strategies for the presentation and interpretation of artworks dealing with sexual violence are needed for museums to redress the patriarchal and colonial presence of sexual violence in their collection.
Keywords: Art Curating; Fine Arts; Museum; Museum Violence; Myriam; Rape; Sexual Violence; Visual activism

“My work opportunities depend on how much I can take” : inappropriate behaviour and harassment in the cultural domain in Finland - Jaakola, Meri (2022)
Phenomena of inappropriate behaviour and harassment are neither new nor unique to the cultural domain. However, these phenomena have not been largely publicly discussed before the 2017 me too movement, presumably due to the culture of silence prominent within the cultural domain. After the movement that started from the film industry and quickly spread around the world, discussion on ethical working conditions has arisen within all the cultural domain as well. This qualitative driven mixed methods research reviews the current situation of inappropriate behaviour and harassment in Finland and seeks to understand the magnitude and forms of the phenomena. The research questions are: 1) What special characteristics or structures in the arts and culture field enable inappropriate behaviour and harassment or the possibility of them? And 2) What can be done to eliminate inappropriate behaviour and harassment from arts and culture workplaces? The research questions are answered analyzing research data collected using a survey and six themed interviews. Research data was collected in the spring of 2021. Topics that surfaced from the survey were used as a basis for the interview questions. Findings from the survey and the interviews act as the thematical scope of this master’s thesis, as they are the most important themes to come out of this research. The main findings of the thesis are that there are four elements that enable and maintain the improper working culture within the cultural domain. The elements are insufficient funding, poor management, artist myth, and limitlessness of the work. These themes are examined in discussion with literature. The four steps this thesis suggests helping uproot the improper behaviour in the cultural domain according to the research data and literature are 1) Pushing for the cultural domain’s ethical board to be established, 2) Composing ethical guidelines for all the cultural domain, 3) Basing funding on following the said guidelines, and 4. Talking about improper behaviour publicly and bringing cases of misconduct forward.
Accepted: 2022-03-30T06:27:19Z Publisher: Taideyliopiston Sibelius-Akatemia

Il était une fois... de trop - Institut national de l'image et du son. (2024)
Une formation pour prévenir le harcèlement en culture.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Sexual Harassment in Display Work: The Case of the Modeling Industry - Crowley, Jocelyn Elise (Gender & Society, 2021)
Keywords: Bibliographie; Cultural industries; Display work; Fashion; Informal industries; Modeling industry; Myriam; Nettoyer; Power dynamics; sexual harassment

Women in the International Film Industry: Policy, Practice and Power - Liddy, Susan (Springer International Publishing, 2020)
Keywords: Irina

How Independent Contractors Respond to Sexual Harassment: The Case of the Modeling Industry - Crowley, Jocelyn Elise (Employee Responsibilities and Rights Journal, 2022)
Sexual harassment continues to be a problem that most commonly affects women in the United States workforce today. While there are legal and organizational remedies available, most of these mechanisms for redress only exist for workers in traditional employeremployee contexts. Independent contractors, self-employed workers who represent a growing number of labor force participants in this economy, can therefore only use informal means of addressing sexual harassment. This study used grounded theory methods to analyze 88 separate narratives of sexual harassment from 70 fashion models, an overwhelmingly female set of independent contractors currently operating in the American economy. The aim of the analysis was to understand the mix and meaning behind the use of informal strategies—more specifically confrontation versus non-confrontation—in response to this sexual harassment. Notably, models most often confronted the perpetrators of harassment. Critically, however, those models who chose non-confrontation did not minimize the abuse that they faced. Instead, they either saw themselves as powerless or engaged in self-blame when faced with harassment on the job.
Keywords: Bibliographie; Confrontation; Fashion industry; Independent contractors; Models; Myriam; Nettoyer; Sexual harassment

The sound of misogyny: sexual harassment and sexual violence in the music industry - McCarry, Melanie; Käkelä, Emmaleena; Jones, Cassandra; Manoussaki, Kallia (Journal of Gender-Based Violence, 2023)
The cultural and creative industries are the fastest growing industries in the UK (). Stakeholder engagement, media reporting, anecdotal evidence and emerging research suggests that there are endemic levels of sexual harassment and sexualised violence within the music industry that can be described as widespread, systemic and normalised. This article reviews the literature on sexual harassment and sexualised violence in the music industry, examining gender stratifications and inequalities within the music industry with a focus on UK, Australian and US studies. The music industry is not a singular entity but instead, is an agglomeration of many different sub-sectors predominantly consisting of three interconnected spheres of music recording and distribution, music publishing and licensing, and live performance. This paper references Kelly’s (; ; ) theorisations on conducive contexts and the continuum of violence to argue that historical and entrenched misogyny and sexism along with the lack of regulation, process and governing frameworks create conditions for both the maintenance of gender inequality and the perpetuation of sexual harassment and sexualised violence within the music industry. Consequently, both the cultural context and the practice of misogyny (in this case sexual harassment and sexualised violence) within the music industry are mutually supporting and reinforcing.
Publisher: Policy Press Section: Journal of Gender-Based Violence
Keywords: Misogyny; Music; Myriam

“The balance of power is me: 0, Harvey Weinstein: 10”: A Critical Discourse Analysis of the press representation of Hollywood’s biggest sexual harassment scandal - Nikolova, Evelin (Women's Studies International Forum, 2021)
On 5 October 2017, The New York Times published an article in which Harvey Weinstein was accused of sexual harassment by five women. The scandal grew to enormous proportions as more allegations against him followed. This led to the #MeToo and TIME'S UP movements, initiatives to fight sexual harassment in the workplace. Given that media discourse can have an impact on the knowledge, beliefs, attitudes, and behaviours of the public regarding these phenomena (van Dijk 1989), this study adopts a Critical Discourse Studies (CDS) perspective and explores how power and gender inequality are sustained, (re)shaped and/or challenged by focusing on the reporting of the Harvey Weinstein case which - to the author's best knowledge - has not been analysed before in the field of linguistics. It draws from the systemic functional linguistics and the discourse-historical approach and it examines the way the perpetrator, the accusers and the phenomenon of sexual harassment were discursively constructed in five key articles published in the New York Times. The findings differ in a major way from existing research on sexual violence against women in that 1) the perpetrator, Weinstein, was depicted with clear ascription of agency, 2) women victims' voices and feelings were foregrounded, 3) the link between sexual harassment and the social context in which it occurs was discussed.
Keywords: Critical discourse studies; Discourse-Historical Approach; Discursive strategies; Media representation; Myriam; Sexual harassment; Transitivity analysis; Weinstein

Music as Labour: Inequalities and Activism in the Past and Present - Abfalter, Dagmar; Reitsamer, Rosa (Taylor & Francis, 2022)
This book brings together research at the intersection of music, cultural industries, management, antiracist politics and gender studies to analyse music as labour, in particular highlighting social inequalities and activism. Providing insights into labour processes and practices, the authors investigate the changing role of manifold actors, institutions and technologies and the corresponding shifts in the valuation and evaluation of music achievements that have shaped the relationship between music, labour, the economy and politics. With research into a variety of geographic regions, chapters shed light on the various ways by which musicians’ work is performed, constructed and managed at different times and show that musicians’ working practices have been marked by precarity, insecurity and short-term contracts long before capitalism invited everybody to ‘be creative’. In doing so, they specifically examine the dynamics in music professions and educational institutions, as well as gatekeepers and mechanisms of inclusion and exclusion. With a specific emphasis on inequalities in the music industries, this book will be essential reading for scholars seeking to understand the collective actions and initiatives that foster participation, inclusion, diversity and fair pay amongst musicians and other workers.
Accepted: 2022-05-18T09:38:24Z
Keywords: Music; Myriam; Personnel and human resources management; bic Book Industry Communication::A The arts::AV Music; bic Book Industry Communication::K Economics; business & management::KJ Business & management::KJM Management & management techniques::KJMV Management of specific areas::KJMV2 Personnel & human resources management; finance

Creative Control: The Ambivalence of Work in the Culture Industries - Siciliano, Michael L. (Creative Control, 2021)
Michael L. Siciliano draws on nearly two years of ethnographic research as a participant-observer in a Los Angeles music studio and a multichannel YouTube network to explore the contradictions of creative work. Creative Control explains why “cool” jobs help us understand how workers can participate in their own exploitation.
Keywords: Myriam; cognitive capitalism; creative labor; digital media; precarity; sociology of labor

‘Put some balls on that woman’: Gendered repertoires of inequality in screen composers’ careers - Cannizzo, Fabian; Strong, Catherine (Gender, Work & Organization, 2020)
This study contributes to debates about gendered career outcomes in the creative industries using data collected in interviews with Australian screen composers. We identify how gendered inequalities are legitimated through professional norms by comparing the responses of screen composers on barriers to women’s advancement. The article explores how three distinct interpretive repertoires help reproduce the gender inequality regime present in the screen composition field. These repertoires are ‘art vs. equality’, where working towards equality can be framed as antithetical to artistic ideals; ‘gendered music’, where men and women are posited as making fundamentally different types of music; and ‘confidence’, where men are framed as innately possessing certain entrepreneurial skills vital to success in the creative industries, while women both shoulder the blame for not possessing such skills and recognize the risks inherent for them in performing confidence. By focusing on repertoires, this study describes the means by which gender-based discrimination is made overt and offered justification among screen composers, posing challenges to organizations and individuals seeking to address gender inequality in the profession.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/gwao.12496
Keywords: Australia; Musique de film; Myriam; composers; creative industries; cultural industries; gender inequality; sexism

Identity work in female-led creative businesses - Martin, Lynn; Jerrard, Bob; Wright, Lucy (Gender, Work & Organization, 2020)
This study explores the identity work carried out by three female owner-managers in creative industry businesses, identified in Government reports as a discriminatory industrial sector for women in the UK. Through the development of narratives by the owners and other participants, observation of practice and review of online and offline materials, three cases emerged. These showed overlapping, different identities developed and performed through identity work. Each presented rational and logical persona as business leaders despite observation showing extensive use of intuition and gut feeling in both creative and entrepreneurial aspects of the business. Intuition and gut feeling were seen as inappropriate at work as they belonged to the home sphere, emotionally based and therefore automatically unreliable. While occupying male stereotypes and avoiding the female realm of emotion at work, these women expressed femininity through their emphasis on the maternal, ‘being a good mother' as a desired ideal being embedded in work as well as home practice.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/gwao.12357
Keywords: Myriam; creative industries; entrepreneurship; gender; identity; innovation

Time for a change: women, work, and gender equality in TV production - Milner, Susan; Gregory, Abigail (Media, Culture & Society, 2022)
This article uses Acker’s concept of inequality regimes to analyze qualitative research findings on work-life balance and gender equality for women in British television production. Female survey respondents, focus group participants, and interviewees spoke of their subjective experience of gendered work practices which disadvantage women as women. These findings build on existing research showing gender disadvantage in the industry, leading to loss of human capital and a narrowing of the range of creative experience. They also show that growing numbers of women are seeking alternative modes of production, at a time of increased awareness of inequality. Such alternatives suggest that change is possible, although it is strongly constrained by organizational logics and subject to continued resistance, in line with Acker’s framework of analysis. Visibility of inequalities is the key to supporting change.
Publisher: SAGE Publications Ltd
Keywords: Myriam; TV; TV production; Television

Challenging gendered power: How sexual harassment perpetrators respond to victim confrontation - Crowley, Jocelyn Elise (Gender, Work & Organization, 2023)
Sexual harassment is a problem that continues to plague mostly women in the American workforce today. One tool that victims can use in these situations is confrontation, either through verbal or physical means. Yet, understudied to this point is how perpetrators respond to confrontation, which is highly salient as to whether this is an effective tool for victims. This study uses grounded theory methods to analyze 31 accounts of sexual harassment from within the fashion industry that recorded perpetrators' responses to victim confrontation to clearly unwanted, abusive behavior. I argue that specific features of the fashion industry, or a “display work culture,” embolden perpetrators to effectively thwart any type of confrontation. Indeed, this study finds that these predominantly male perpetrators of sexual harassment moved to reassert their dominant position over their female victims in the moment of confrontation, immediately after being confronted, and even later, well beyond confrontation, as they aimed to reestablish normal business practices as usual. This research thus dispels a significant sexual harassment myth that victims working within this culture are able to stop perpetrators simply by speaking up and/or fighting back and points to the need for the development of sexual harassment theory to incorporate work culture-related risk factors and remedies.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/gwao.12906
Keywords: Bibliographie; Myriam; Nettoyer; confrontation; display work culture; fashion industry; perpetrators; sexual harassment

What else can a crush become: working with arts-methods to address sexual harassment in pre-teen romantic relationship cultures - Huuki, Tuija; Kyrölä, Kata; Pihkala, Suvi (Gender and Education, 2022)
Keywords: Myriam

Re-Cognizing Harassment with the Arts - Babulski, Timothy (Phenomenology & Practice, 2022)
Absent mechanisms of restorative justice, victims of sexual harassment, particularly those within the LGBT+ community that are already frequent targets of relational aggression, are unlikely to either report or reckon with the consequences of inappropriate workplace behaviors and discrimination. Written from the perspective of a masculinized bisexual whose encounter with a pervasive culture of sexual harassment and psychological abuse provoked suicidal ideation, this paper employs the artistic practices of illustration as a means of first re-cognizing and recognizing phenomena, a Ricœurean construct of narrative and a palimpsest of multivocal text and images to evoke the lived experience of harassment and an analytic layer to invoke the phenomenon. By drawing, writing, and thinking through the phenomenon, the marriage of artistic and phenomenological approaches allows both researcher and reader to confront the ‘painful truths’ that otherwise resist easy analysis.
Number: 2
Keywords: LGBTIQ; Myriam; Safe spaces; Teaching arts; Visual arts

Title IX, Esports, and #EToo - Stoever, Jane K (The George Washington Law Review, 2021)
As colleges and universities increasingly award video gaming scholarships, field competitive esports teams, construct esports arenas in the centers of campuses, and promote student interaction through gaming, schools should anticipate the sexual cyberviolence, harassment, and technology-enabled abuse that commonly occur through gaming.
Keywords: Bibliographie; Irina; Nettoyer

Gendered Barriers In The Gaming Industry - Singh, Tanya (Journal of Sports Law, Policy and Governance, 2020)
As of 2019, there are an estimated 2.5 billion garners globally. Roughly half of all garners are female. Despite the figures, there is a serious underrepresentation of female gainers in the professional gaming and game development community. It is thus important to examine the underlying causes hindering equally capable female gainers and game developers from pursuing a serious career in gaming, at par with their male counterparts.In this article, the authorexamines the impact of the culturalassociationof games with the male demography, stereotypes andstructuralbarrierslimiting women from realizing theirfullpotential, female representation in video games and workplace, pervasive misogyny and sexual harassment of women across all levels in the industry, and lastly, the steps that can be taken to better the status quo in favour of women.
Keywords: Bibliographie; Irina; Nettoyer

A More Pixelated Union: A Look at the Path to Unionization in the Video Game Industry under Trump's National Labor Relations Board - Selfridge, William C. (2021)
Keywords: Irina

Review: Cooperative Gaming: Diversity in the Games Industry and How to Cultivate Inclusion - Hanussek, Benjamin (Press Start, 2022)
Review: Cooperative Gaming: Diversity in the Games Industry and How to Cultivate Inclusion, by Alayna Cole and Jessica Zammit. 2020. CRC Press. xv + 95 pp.
Number: 2
Keywords: Irina; diversity; game industry; game studies; inclusion

Exploring Vicarious Liability to Remedy the #E-Too Movement - Hewson, Eloise (York Law Review, 2022)
The esports, or competitive video gaming, industry is an exciting area of economic and cultural growth. Gaming can facilitate interpersonal connection, shared problem-solving, and creativity. Players may purchase a game, watch a streamer play it online, join an online gaming community, attend a tournament, compete professionally, or find employment in game development or a related field. The gaming industry generates enormous economic value and employs tens of thousands of people in the UK alone. However, the esports sector does not extend its benefits equally. Women are regularly verbally harassed in video games, countless women have been groped at esports events, women have been raped by professional players, underage fans have been groomed. Abuse is endemic to online gaming communities.
Keywords: Bibliographie; Irina; Nettoyer

Narrating women workers’ perceptions of sexism and change in the Australian screen postproduction sector before and after #MeToo - Dooley, Kath; Erhart, Julia (Feminist Media Studies, 2021)
This article interrogates the localized experiences of present-day workers who identify as women in Australian postproduction sectors, including editing, visual effects (VFX), and animation, exploring sex ism and perceptions of change in the age of #MeToo. Considering the significant numbers of women working in these sectors, and the scant research into their experiences undertaken in an Australian context, the authors conducted semi-structured interviews with ten women in various roles and in various geographical locations in Australia. This qualitative approach to data collection aims to explore inequalities that may not be captured in industry surveys, providing fine-grain details of the ways that individuals in postproduction experience sexism. The resulting data suggests that while there is continuity between the gendered experiences of these workers and that of women in industry sectors that have already been documen ted, there are, however, new observations about changes in work place behavior in the sector, brought about by growing public awareness of industry discrimination and harassment and of shifts in Australian industry policy. The authors isolated recurring themes within women’s gendered experiences in relation to how they per ceived the impact of the gender-equity initiatives on the attitudes of their co-workers, their workplace opportunities, and their experi ences as workers.
Keywords: Irina

The Routledge Companion to Romantic Love - Brooks, Ann (Routledge, 2021)
Keywords: Irina

Working with “monstrous men”: ambivalent sexism in the Bombay film industry - Sanchez Lozoya, Zeltzyn Rubi (Feminist Media Studies, 2022)
In India, the 2012 Delhi gang rape case catalyzed protests for women’s rights, particularly in regard to their safety. These demands were rekindled with vigor anew with the eruption of the #MeToo movement. In the Indian film industry, the most visible change appeared in the gradual increase of films with womenleads. But behind the scenes, there has been comparatively less change in female representation. Currently, approximately less than 10% of film directors in India are women. Considering the impor tance of having stories about women being made by women, in this article I examine the factors that hinder women’s entrance and tenure in the Mumbai film industry. I argue that a composite of concerns, including but not limited to reputability and personal security, thwarts women’s progress in the industry. I base my con clusions on interviews with women and men working in the film industry, conducted in Mumbai in 2017. I use the framework of the Ambivalent Sexism Index developed by psychologists Glick and Fiske in 1996, and revised in 2013, (1996, 2001, 2013) to examine my interviewees’ encounters with hostile and benevolent sexism. This article complicates our understanding of the reasons that limit the work of women beyond explanations of overt discrimination.
Keywords: Irina

#metoo: The Good, the Bad, and the Backlash - Tranchese, Alessia (From Fritzl to #metoo: Twelve Years of Rape Coverage in the British Press, 2023)
I start this discussion in this chapter with an outline of the key points within the #metoo debate, looking at what, according to various scholars, has and has not been achieved since the hashtag went viral in 2017. This overview constitutes the context for the subsequent analysis and critical evaluation, which will look at how the press conceptualised #metoo, and how it shaped some of the wider discussions about the hashtag. In Chapter 11, it will focus on whether (and how) the widespread use of #metoo after 2017 affected the representation of violence against women in the British press compared to the previous years.
Keywords: Irina

Non-Consensual Sexual Contact at Electronic Dance Music Parties - Palamar, Joseph J.; Griffin, Marybec (Archives of Sexual Behavior, 2020)
Non-consensual sexual contact in bars is common, but few studies have focused on the extent of this problem at electronic dance music (EDM) parties, which are growing in popularity. We aimed to estimate prevalence and correlates of non-consensual sexual contact among individuals who attend EDM parties in New York City (NYC). Adults (ages 18–40 years) entering EDM parties in NYC were surveyed in 2018 using time–space sampling. Participants (n = 1005) were asked whether they had experienced unwanted or uninvited sexual contact including unwanted groping, kissing, or touching at an EDM party. We estimate that 15.2% of EDM party attendees in NYC have experienced non-consensual sexual contact at such parties. The majority (62.5%) of those reported that it occurred 1–2 times and 49.1% were usually or always drunk or high during the encounter(s). Almost all women experiencing non-consensual contact (99.5%) were all or mostly touched by men; 38.6% of men were all or mostly touched by other men. Women were at more than twice the odds of reporting non-consensual sexual contact than men (aOR = 2.38, p < .05) with 21.8% of women reporting experiencing non-consensual sexual contact compared to 11.0% of men. Among women, those ages 18–24 were at over twice the odds (aOR = 2.75, p < .05) of experiencing non-consensual sexual contact than those ages 25–40. EDM party environments can increase susceptibility to non-consensual sexual contact. Prevention needs to be geared toward those at risk, and education is needed for those likely to commit non-consensual sexual contact.
Keywords: Dance music; Drug use; Non-consensual sex; Sexual assault

#ThisIsArtSchool Is Exposing Allegations Of Racism & Sexual Abuse In Montreal Universities - Elliot, Teddy (MTL Blog, 2020)
As stories of racism and discrimination towards Black, Indigenous, and people of colour continue to dominate public discourse, more and more shocking allegations come to light about the lived experiences of systemic racism.
Keywords: Bibliographie; Nettoyer

Designing Women: Learning from Feminist Legacies and the Women-In-Games Movement - Schoemann, Sarah (Georgia Institute of Technology, 2021)
In 2019 the video games industry was rocked by a slew of high-profile sexual harassment and assault allegations that some called the #MeToo movement of the games world, but to many these revelations came as no surprise. From the 2004 EA Spouse controversy to the 2014 #Gamergate harassment campaign the games industry has long been known for harboring an at times toxic atmosphere of exploitation and discrimination. This project looks at a handful of Women-In-Games organizations that set out to change the experience of women in the industry by helping newcomers to gain high tech skills and to supporting early career professionals through mentorship and community building. Along the way, it combines the study of these Women-In-Games organizations with a years-long collaboration bringing video games to the US' oldest feminist bookstore, Charis Books & More in Atlanta, GA. Through examining the work and values of two types of organizations devoted to women's equality, one a historic feminist movement-building space and the others, contemporary interventions into the professional games and tech industry, this study asks the questions "What can the Women-In-Games movement learn from the rich history of feminist organizing at spaces like Charis?" "Can games play a part in feminist movement building?" and "What does the future of feminist organizing look like in the games industry?”
Accepted: 2021-09-15T15:43:41Z Publisher: Georgia Institute of Technology
Keywords: Bibliographie; Irina; Nettoyer

Cooperative Gaming: Diversity in the Games Industry and How to Cultivate Inclusion - Cole, Alayna; Zammit, Jessica (CRC Press, 2020)
Description Cooperative Gaming provides context and practical advice regarding diversity in the games industry. The book begins with a deep dive into research literature and the history of diversity in the games industry to provide context around what diversity is and why it is a topic worth considering. The book looks at the different facets of diversity and games, exploring the issues and solutions within game development, studio management, event planning, and more. It provides people with practical advice about being a marginalized person in the games industry and how to be heard, how studios can support inclusive practices, and events can actively become more accessible to a diverse audience. Key Features • Explores the history of diversity in games • Provides important information around what it is like to be a marginalized person in the industry • Gives practical steps to improve the inclusivity of the industry that are designed to aid in contextualizing and upskilling new developers Author Bios Alayna Cole is the managing director of Queerly Represent Me, a not-for-profit championing queer representation in games. Alayna is also a producer at Sledgehammer Games, co-chair of the IGDA LGBTQ+ special interest group, and an award-winning games journalist and game developer. She was featured on the 2016 and 2017 Develop Pacific 30 Under 30 lists and the 2017 and 2019 Develop Pacific Women in Games lists, and she has received several other accolades in the industry. Jessica Zammit started writing in 2013 for Start Select Media, and for the next five years she followed her interest in writing about representations of mental health, diversity, and particularly, sexuality in video games. Jessica has been speaking about diversity in games at conventions such as PAX Australia since 2016 and has been featured on several other discussions in and around the topic of representation in games and games criticism. Along with her co-author, she is co-chair of the IGDA LGBTQ+ special interest group, and she was featured on the 2018 Develop Pacific 30 Under 30 and Women in Games lists.
Google-Books-ID: 0XjtDwAAQBAJ
Keywords: Computers / Programming / Games; Irina

Let Her Play: A report on gender-based violence in video games - Mettler, Kirsten (Embodied: The Stanford Undergraduate Journal of Feminist, Gender, and Sexuality Studies, 2022)
Globally, video games are a $152 billion industry, and approximately 3.1 billion people, or 40% of the population, are players (Ingersoll & Anti-Defamation League, 2019, Price, 2020). Gaming is a huge industry, and it’s only getting bigger. Unfortunately, women and other historically marginalized groups often face staggering levels of harassment and violence in these communities. This report aims to explore the issue of gender-based violence in video games by analyzing contributing factors and proposing gaming company interventions.
Number: 1
Keywords: Bibliographie; Irina; Nettoyer; esports

We protect animals well": A structural approach to abusive conduct within circus schools - Matthis, Rosa (Linköping University, 2021)
This master thesis investigates abusive conduct in circus schools. Focus is put on the management level in order to achieve and provide knowledge of measures and attitudes related to prevention. Th ...
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Why #MeToo Hasn’t Transformed the Stand-Up Scene - Baum, Gary (The Hollywood Reporter, 2021)
Female comics say that the empowerment movement has been met with pushback, retaliation and mockery from male counterparts: “If you’re a woman who’s been harassed, if you just talk about what happened, people perceive you as being some ‘cancel culture’ advocate.”
Keywords: Sophie-Anne

Unwanted Sexual Attention in the Night-Time Economy: Behaviors, Safety Strategies, and Conceptualizing “Feisty Femininity” - Gunby, Clare; Carline, Anna; Taylor, Stuart; Gosling, Helena (Feminist Criminology, 2020)
Almost nothing is known about ?unwanted sexual attention? and women?s navigation of it when in bars and nightclubs. Using focus group discussions, this article addresses that gap. It develops knowledge of the behaviors that constitute unwanted, the safety strategies used to manage them, and examines how these practices underpin gender performance in night-time spaces: environments renowned for the dilemmas they pose to women. We then use these data to develop the concept ?feisty femininity? to highlight a neglected form of femininity that overtly resists unwanted encounters. This femininity can arguably play a role in efforts aimed at ending gendered violence.
Publisher: SAGE Publications

Are Female Clowns Politically Incorrect? A Case Study on Female Clowns’ Political Engagement at the 7th “Esse Monte de Mulher Palhaça” festival in Rio de Janeiro - Cézard, Zed (Cadernos de Arte e Antropologia, 2020)
By linking the notion of politics with clown practices played out during the biennial festival «Esse Monte de Mulher Palhaça» in Rio de Janeiro (2018), dedicated specifically to female clowns, the relations between politics and feminism are raised, as well as the question of the place of clowns and women within the social system in which they act. In addition to reassessing the concept of politics through this new field of application, looking at what artistic practices convey or denounce as inequalities, allows us to identify politicized and political social elements. The private sphere, the power relations, the importance of gender, and the body and sexuality as treated in the festival’s performances raise political issues. We are lead to think of the phenomenon of Brazilian female clowns as a political space of claims, in particular feminist ones, and a resistance to dominant sexist normativity.
Keywords: Bibliographie; Brazil; Nettoyer; Sophie-Anne; female clowns; feminism; activism; politics

Understanding Sexual Harassment in the #MeToo Era - Julios, Christina (Sexual Harassment in the UK Parliament: Lessons from the #MeToo Era, 2022)
This chapter provides a contextual account of the rise of #MeToo as an global gender-equality campaign supporting those affected by sexual transgressions. Originally articulated by African-American civil rights activist Tarana Burke in 2006, the slogan ‘me too’ was meant as a rallying cry to support young minority ethic survivors of sexual abuse. Years later, social media would turn Burke’s motto into a byword for the global #MeToo movement. The chapter chronicles the events surrounding #MeToo’s inception, including Hollywood producer Harvey Weinstein’s sexual exploitation scandal in 2017, and The New York Times and The New Yorker exposés of his serial offending within the film industry. It also examines the narratives of countless survivors and #MeToo campaigners, including high-profile cases such as those of Rose McGowan, Alyssa Milano, Mimi Haleyi, Jessica Mann and Zelda Perkins. The chapter then critically considers the growth and international significance of #MeToo as well as its inherent shortcomings.
Keywords: #MeToo; Farrow; Harvey Weinstein; Irina; Kantor and Twohey; Rose McGowan

#TimesUp on Individual Litigation Reform: Combatting Sexual Harassment through Employee-Driven Action and Private Regulation - Dugan, Natalie (Columbia Journal of Law and Social Problems, 2020)
Keywords: Bibliographie; Irina; Nettoyer

Now About All These Women in the Swedish Film Industry - Wallenberg, Louise; Papadopoulou, Frantzeska; Koskinen, Maaret; Soila, Tytti (Bloomsbury Academic, 2023)
In the aftermath of the MeToo movement, during an ongoing pandemic, and in the midst of repeated demands for a 50/50 split between men and women in above-the-line positions, this book analyzes and interrogates the politics of gender focusing on the Swedish film industry, often considered to be the most "gender equal" film industry worldwide. While this gender equality (with a considerable proportion of women behind the camera) is much due to policies carried out of the state funded Swedish Film Institute, women filmmakers in Sweden still struggle with the same problems as do women in other national film industries. These problems entail having smaller production and distribution budgets than men and working in an environment involving recurring scandals of gender discrimination and sexual harassment. This open access book looks behind the statistics and explores the often complex cultural, legal, and political conditions under which women have entered a male-dominated industry and discusses women’s strategies and efforts to promote change while providing evidence on how women’s presence has challenged the industry by provoking critical reactions and introducing new ways to portray women on screen. Using a wide range of different sources (e.g. archival material, laws, contracts, films, biographical materials, and interviews), the book tells the history of the rise of gender equality efforts undertaken by the Swedish Film Institute and investigates women’s possibilities to manage the rights to their work. It offers compelling portraits of pioneering women who have worked in or in relation to the industry and looks at the experiences of women currently working in the film industry. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Örebro universitet.
Accepted: 2023-02-09T13:06:14Z
Keywords: Irina; Metoo; Sweden; Swedish Film Institute; TV & radio::APF Films; change; cinema::APFA Film theory & criticism; cinema::APFN Film: styles & genres; conditions; discrimination; equality; film industry; filmmakers; male-dominated; pioneering; politics of gender; rights; scandal; sexual harassment

The impact of #MeToo in the South African film and television industry, within a historical framework - Majiba, Ntsika (Université de l'Afrique du Sud, 2022)
The study is a history project and is concerned with tracking the impact of #MeToo in the South African Film and Television industry in South Africa. Its main premise were the findings made public by a South African organization, Sisters Working in Film and Television (SWIFT) in 2017, that found that sexual harassment in the television and film industry was not just a norm but a crisis. The core focus of the study was on the development and impact of the #MeToo movement, which entailed investigating the manner in which women reacted to the hashtag (#MeToo), the reaction of their male counterparts, as well as the reaction and actions taken by the various bodies, institutions and organisations in the Film and Television industry, which included; broadcasters and production houses alike. This study begins by giving a concise background of the movement by firstly, historicising various female-led movements and comparing and contrasting them with the rise of digital movements or digital activism. The historicisation involves a brief comparison of past and present women-led activism, as well as a brief review of other hashtags like #AmINext and #Enough, on which #MeToo has had an influence. It goes on to investigate the development of #MeToo movement and to discuss the responses of the industry and individuals to the movement. The study embarked on a data collection quest by interviewing eleven female television and film practitioners in South Africa. Their ages ranged from 20 to 55. The findings of the research revealed that female practitioners were still being harassed post #MeToo, although subtly. The lack of unity amongst women in the sector was cited as one of the reasons behind the ongoing harassment. Gender parity and equity was also still lacking in the South African television and film industry. This study emerged in the midst of activism and scholarship seeking to unravel the norms of South African sexual harassment and rape culture against women. Thus, the study focused on the changes and transformations brought about by the hashtag within the industry. With South Africa’s historical background and the current circumstances around Gender Based Violence (GBV), this study was concerned with tracking whether or not digital activism had in some way been able to aid change and transformation. In particular, this study looked at the impact of the MeToo phenomenon on the women in the industry, the extent to which it empowered them, what they began to say and how they began to act. The study also explored South Africa’s ‘rape culture’ as South Africa has been proclaimed the ‘worlds rape capital’. It reflected on the colonial rule as the perpetuation of patriarchy and male entitlement over female bodies. Patriarchy in the industry was also confirmed by the findings and through data analysis, as one of the key factors in the emergence of #MeToo in South Africa, and in the utilisation of the hashtag by women in the sector to speak up against sexual harassment.
Accepted: 2023-02-20T11:59:11Z
Keywords: Bibliographie; Irina; Nettoyer

Experiencing Male Dominance in Swedish Film Production - Jansson, Maria; Wallenberg, Louise (Women in the International Film Industry: Policy, Practice and Power, 2020)
Sweden has been hailed for its recent success in increasing the number of female directors, scriptwriters and producers. Published reports, panel discussions and a vast number of press conferences on the pressing matter of gender equality within the industry together with a 5050 quota have all put the Swedish film industry—and its CEO Anna Serner—on the map. However, the last couple of years has disclosed several scandals regarding sexism and discrimination in the Swedish film industry—just as in other national film industries. This paper sets out to discuss how female film workers (e.g., directors, actors and producers) understand and negotiate their experiences of male dominance within their work context. Based on a series of interviews with women working in Swedish film from the early 1960s until today, we analyze similarities and differences in experiences as well as how these experiences are explained by the interviewees. Their stories are analyzed by using feminist institutional theory to understand how policy, funding schemes and other institutional aspects are intertwined with their experiences. The paper sets out to analyze three themes: (1) comments and suggestions during production and post-production regarding female protagonists; (2) experience of gender trouble in the process of fundraising; and (3) strategies used by the interviewed filmmakers to produce a more women-friendly environment during productions.
Keywords: Irina

Gender Equality in British Film-making: Research, Targets, Change - Cobb, Shelley; Williams, Linda Ruth (Women in the International Film Industry: Policy, Practice and Power, 2020)
In October 2017, the British Film Institute declared that it would commit to specific targets for gender equality and diversity in key production roles on films with support from the Film Fund. This decision by the BFI to set targets, arguably, did not come just from their own diversity and inclusion goals. Activist film-makers had previously called for targets for the Film Fund, especially for women directors. This chapter will give an accounting of the current state of gender (in)equality in the UK industry by: outlining new research that has clarified the stagnant inequality in the UK film industry; articulating the key role of a network of activist groups (that include researchers, professional and campaigning bodies, exhibitors and film-makers) to bring attention to the problem; putting pressure on the film industry and public bodies; and summarising institutional responses to that pressure since 2016, with a critical analysis of the potential and limits of the BFI’s relatively recently implemented diversity and equality targets.
Keywords: Bibliographie; Irina; Nettoyer

A Balancing Act: Agency and Constraints in University Students’ Understanding of and Responses to Sexual Violence in the Night-Time Economy - Anitha, Sundari; Jordan, Ana; Jameson, Jill; Davy, Zowie (Violence Against Women, 2021)
This article extends our understanding of how university students make sense of, and respond to, sexual violence in the night-time economy (NTE). Based on semi-structured interviews with 26 students in a city in England, we examine students’ constructions of their experiences of sexual violence within the NTE, exploring their negotiations with, and resistance to, this violence. Building upon theories of postfeminism, we interrogate the possibilities for resistance within the gendered spaces of the NTE and propose a disaggregated conceptualization of agency to understand responses to sexual violence, thereby offering useful insights for challenging sexual violence in the NTE and in universities.
Keywords: Camille

Sexual violence and nightlife: A systematic literature review - Quigg, Zara; Bigland, Charlotte; Hughes, Karen; Duch, Mariangels; Juan, Montse (Aggression and Violent Behavior, 2020)
Preventing and responding to sexual violence in nightlife settings is increasingly of global concern. The goal of this article was to identify and summarise academic studies on nightlife-related sexual violence. Specifically, to explore the nature, extent and consequences of, or associations with nightlife-related sexual violence, and interventions to prevent and respond. Of the 61 studies identified, 29 explored or reported on the nature of nightlife-related sexual violence, 22 provided information on extent, 38 on associations, and 19 on prevention and response. The majority of studies had been implemented in the past ten years (2009–2018) and in high-income countries. The review illustrates that nightlife-related sexual violence is pervasive, with lifetime prevalence reaching over 50% amongst numerous study samples. Studies suggest that a combination of factors at an individual, relationship, and community/environmental level is associated with nightlife-related sexual violence. No studies directly explored consequences, and few studies evaluated prevention and response approaches. Globally, further research is required to understand nightlife-related sexual violence, and inform the development of prevention programmes across all but particularly low and middle-income countries. Critically, interventions aimed at preventing and responding to nightlife-related sexual violence require thorough evaluation, with findings disseminated in both lay and academic literature.
Keywords: Bars; Bibliographie; Nettoyer; Nightlife; Prevention; Rape; Sexual; Violence

Gendered Responses to Gendered Harms: Sexual Violence and Bystander Intervention at Australian Music Festivals - Baillie, Greta; Fileborn, Bianca; Wadds, Phillip (Violence Against Women, 2022)
Bystander intervention has shown promise in preventing sexual violence in certain social contexts. Despite emerging evidence of pervasive sexual violence at music festivals, no research has considered bystander intervention in this setting. Drawing on an online survey conducted with 371 Australian festival attendees, we explore the role of gender on bystander intervention at music festivals. Findings point to significant gender differences, with women more willing and likely to intervene in a broader range of scenarios. We argue that responses to sexual violence are a collective responsibility shared by both women and men, as well as festival organizers and industry bodies.
Keywords: Camille

Sexual harassment and violence at Australian music festivals: Reporting practices and experiences of festival attendees - Fileborn, Bianca; Wadds, Phillip; Tomsen, Stephen (Australian & New Zealand Journal of Criminology, 2020)
Despite the well-documented under-reporting of sexual violence, to date, no research has considered reporting practices within the specific context of music festivals. Drawing on 16 in-depth interviews with victim-survivors, this article examines survivors’ experiences of (non)reporting sexual violence in festival settings. We argue that while some barriers to reporting are shared across contexts, others play out in context-specific ways. Our research argues that the liberal, often transgressive culture of music festivals, combined with site-specific policing practices and spatial context, creates unique impediments to reporting with particular implications in responding to, and aiming to prevent, sexual violence at music festivals.
Keywords: Bibliographie; Camille; Nettoyer

Indian Women in Comedy: : An Inquiry into the Perpetuation of Rape Culture on Social Media - Sharma, Mridula (Sanglap: Journal of Literary and Cultural Inquiry, 2021)
‘Postfeminist’ society has created the impression that contemporary discourses on gender representation, particularly in digital media platforms, are pointless. This misconception is coupled with online aggression by men’s rights activists who position feminist debates as sources of male oppression. However, media practices and consumption processes continue to maintain the supremacy of the male gender identity, which strengthens the process of transforming social media into a component of the “manosphere.” The failure of the fourth wave of feminism in utilising the Internet for mobilising activism for the ontological equality of all genders has succeeded by increasing gender-based violence against women. Indian women in comedy negotiate with these systemic inequalities while navigating male dominance in the comedy industry. The paper is an attempt to examine the structures of gender inequality and bias that affect the participation and advancement of women in the comedy circuit. Its focus remains on the formulation of a rape culture on social media and its subsequent consequences in the larger social context of the development of a patriarchal culture.
Number: 2
Keywords: Digital Abuse; Sophie-Anne

Laughter from the Sidelines: Precarious Work in the Canadian Comedy Industry - Trusolino, Madison (Creative Industries in Canada, 2022)
Creative Industries in Canada is a foundational text that encourages students to think critically about creative industries within a Canadian context and interrogate the current state and future possibilities of the industry. While much of current creative industries literature concerns the United Kingdom, the United States, and Asia, this text captures the breadth of how Canadian industries are organized and experienced, and how they operate.This ambitious collection aims to guide students through the current landscape of Canadian creative industries through three thematic sections. “Production” collects chapters focused on how national discourses and identities are produced through creative industries and the tensions that exist between policy and media. “Participation” explores how we engage with these industries in different roles: as consumer, creator, policy-maker, and more. “Pedagogies” explores how education impacts inclusion and visibility in creative industries.Truly intersectional, Creative Industries in Canada provides students with practical industry knowledge and frameworks to explore the current state of the field and its future. With a broad application to many undergraduate programs, this text is a must-read resource for those pursuing media studies, arts management, creative and cultural industries studies, communications, and arts and humanities.
Keywords: Bibliographie; Business & Economics / Industries / Media & Communications; Nettoyer; Social Science / Media Studies; Sophie-Anne

Sexual Violence and Gender Equality in Grassroots Music Venues: How to Facilitate Change - Hill, Rosemary Lucy; Megson, Molly (IASPM Journal, 2020)
Sexual violence in the music industry is known to impact negatively on women’s participation. We examine how grassroots venues and promoters can implement changes to tackle sexual violence and work towards gender equality. We draw on UK-based, impact-focused research which sought to raise awareness of sexual violence, and to facilitate anti-violence changes within organisations. We find that working across a city’s music scene and engaging with oversight organisations such as local authorities can aid in persuading venues and promoters to seek training. However, for individuals leading on changes, personal experiences of sexual violence as a victim/survivor or bystander are important factors in their decision. We conclude that men in the music industry need to become more aware of the need for change, and willing to act on that awareness; and that more women need to own, manage, and run venues and events.
Keywords: Bibliographie; Gender; Nettoyer; live music; music industry; music venues; prevention; sexual violence

'Urban' no more: black British music execs call for industry reforms (the Guardian, 2020)
Open letter from new group seeks action on racism and better career development
Section: Music

Gendered Violence at International Festivals: An Interdisciplinary Perspective - Platt, Louise; Finkel, Rebecca (Routledge, 2020)
Gendered Violence at International Festivals is a groundbreaking collection that focusses on this highly important social issue for the first time. Including a diverse range of interdisciplinary studies on the issue, the book contests the widely held notion that festivals are temporal spaces free from structural sexism, inequalities or gender power dynamics. Rather, they are spaces where these concerns are enhanced and enacted more freely and where the experiential environment is used as an excuse or as an opportunity to victim blame and shame. In this emerging and under-researched area, the chapters not only present original work in terms of topics but also in theoretical and methodological approaches. All of the chapters are cross- or interdisciplinary, drawing on gender, sexualities, cultural and ethnicity studies. Studies from a range of highly regarded academics based around the world examine the subject by looking at examples from a wide range of destinations, including Spain, Argentina, Nigeria, Zimbabwe, Australia, Canada and the UK. This significant book progresses understanding and debates about gendered festival experiences and emphasises the symbolic and physical violence often associated with them. This will be of great interest to, undergraduate and postgraduate students and academics in the field of Events Studies. It will also be of use to practitioners or non-profit workers in the festival industries, including festival management organisations and planning committees.
Google-Books-ID: Q6bYDwAAQBAJ
Keywords: Business & Economics / Industries / Hospitality; Travel & Tourism

Teaching Tertiary music in the #metoo era - Devenish, Louise; Sun, Cecilia; Hope, Cat; Tomlinson, Vanessa (Tempo, 2020)
Abstract Over the past two decades significant changes in approaches to gender equity have taken place in the fields of contemporary music and music research. However, women in music are still disadvantaged in terms of income, inclusion and professional opportunities. In Australia a national approach to improving gender equity in music has begun to emerge as once-controversial strategies trialled by four tertiary institutions have become established practices. This article discusses successful inclusion strategies for women in music, including the commitment to gender-balanced programming across all concerts at Queensland Conservatorium of Music by 2025, the introduction of mandatory quotas in recital programmes at Monash University, mentoring programmes for women composers at Sydney Conservatorium of Music, and the development of coursework devoted to women in music at The University of Western Australia, as well as other initiatives that have emerged from them, both within and beyond the institution. Each approach is examined in the context of broader global discussions around gender and feminism. The public willingness to engage in discussions over sexual harassment, sexual assault and gender discrimination in the workplace that has resulted from the #MeToo movement is cited as key in influencing the engagement of students and professionals with these strategies and subsequent influence on performance practices, project development and presentational formats in new music.
Keywords: Myriam

Sexual violence at live music events: Experiences, responses and prevention - Hill, Rosemary Lucy; Hesmondhalgh, David; Megson, Molly (International Journal of Cultural Studies, 2020)
Recent media reporting has highlighted that incidents of sexual violence frequently occur at live music events. Sexual violence has significant impacts on the health of those who experience it, yet little is known of how it impacts on everyday engagements with music, nor what measures venues and promoters might take to prevent and respond to incidents. Through interviews with concert goers, venue managers, promoters and campaigning groups, we investigated experiences of sexual violence at indie, rock, punk and funk gigs in small venues in one English city. We show that sexual violence at live music events significantly impacts on (predominantly) women’s musical participation. We argue that venues and promoters must work proactively to create musical communities that act as a defence against the normalisation of sexual violence, taking inspiration from safer space policies.
Keywords: Camille; gender; live music; prevention; safe spaces; sexual violence; unwanted sexual attention